PTS and the built environment in George Town, Penang - Mohamad, Diana; Saji, Nurdalila (The International Institute for Science, Technology and Education (IISTE), 2012)
Urban development is complex and contested. This complexity brings forward the realization that urban development’s success is something that depends not only on the way it is designed but also stimulated by people’s acceptance level as well as the government’s commitment. Observation on the study area and its surrounding environment shows a unique landscape where buildings were ranged into several urban development classifications. In this case specifically, this paper adopts the view that ‘...there is no distinct boundary between specific types of development [given that] the decisions on the location of the actual boundaries are frequently made quite arbitrarily’ (Zaremski, 2006 pp 315-316), between the study area and its surrounding environment. This paper investigates the complexities facing a range of key stakeholders groups in managing and developing George Town where the unique landscape suggests the presence of social, cultural and economic inequalities are still being literally instilled into George Town’s development.